Documented Meranaw Folktales of Lanao: An Archival Collection and Study for Instructional Materials - Ismael, Farraniva S. Acmed (Randwick International of Social Science Journal, 2025)
Meranaw folk literature is a rich collection of folktales, myths, legends, fables, riddles, epics, and proverbs. The primary objective of this research is to gather, organize, and analyze documented Meranaw folktales from Lanao to preserve and enhance the understanding of these oral traditions. As a vital component of the region's cultural heritage, Meranaw folktales offer profound insights into the values, beliefs, and social conventions of the Meranaw community. Despite their cultural significance, these narratives have often been overlooked in scholarly research due to their dispersal across various archival sources. The study employed a mixed-methods approach, utilizing qualitative content analysis and quantitative data collection. Archival research was conducted to compile data on documented Meranaw folktales, with data collection taking place at various locations in Lanao del Sur, where narrative texts are preserved, followed by content analysis to categorize themes and cultural elements present in the folktales. The quantitative analysis identified the number and distribution of folktales across reference materials. The findings revealed a total of 143 documented Meranaw folktales, which were published and distributed across six reference materials. Based on the analysis, the researcher developed instructional materials, explicitly reading resources derived from Meranaw folktales, supplemented with a glossary, illustrations, and learning activities to serve as educational aids for Mother Tongue and literature subjects.